The role of financial slack in moderating the effect of ESG on firm performance in sharia & non-sharia - Ramadhani, Ikhlassenina; Wardiwiyono, Sartini; Shofiyah, Indah (Proceeding International Conference on Accounting and Finance, 2026)
This study aims to examine the effect of ESG on company performance and the role of financial slack in moderating the relationship between ESG and company performance in 9 countries with the highest Islamic financial assets. A total sample of 686 companies was analyzed using panel data and processed with STATA as the analytical tool. The results show that ESG has a significant effect on company performance as measured by ROE. However, financial slack does not play a moderating role in the relationship between ESG and company performance. This study focuses only on companies in the 9 countries with the highest Islamic financial assets, considering that Islamic principles may serve as a foundation for ESG practices to improve company performance. Sharia compliance, measured using a dummy variable, is included as a control variable to observe its effect on company performance.